The Construction of Presence and the Multimidiatic Stage: hegemony of an immanent presence - Nunes, Juarez José; Baumgartel (Universidade do Estado de Santa Catarina – UDESC, Florianópolis/SC, Brazil), Stephan (Revista Brasileira de Estudos da Presença, 2022)
In this work, we depart from the understanding that the co-presence of performers and spectators in contemporary theatre articulates itself through a focus on fiction and one that emphasizes the sensorial perception and concrete interaction. Based on a discussion of the problem of expression in Deleuze/Spinoza and on the critique of the production of meaning in Gumbrecht, we name these two modes of presence respectively emanative presence and immanent presence, with the latter becoming hegemonic in contemporary theatre. We aim to reflect on how a multimedia device, with its possibilities of intermediality, may impact on the interaction between immanence and transcendence.